Analisis Permasalahan Belajar Pada Anak Sekolah Dasar - Annisya Ayu Sutrisna; Diandra Nazwa Aulia Ruswandi; Pretty Septriani Tambunan; Maysyarah Maysyarah; Khairunnisa Khairunnisa (Departement of Mathematics Education, 2024)
Various problems in the educational process of elementary school students create significant challenges for teachers who are responsible for their learning. Intensive efforts are required as there are many factors involved. The solutions implemented by the teacher during learning are very important. Researchers used a library research approach by investigating a number of national journal sources and articles relevant to the research topic. The analysis shows that educational problems in elementary schools are influenced by internal factors of students and external factors from the environment. To overcome the learning challenges of children at primary school age, basic learning design is needed that involves appropriate methods, models and media so that learning objectives can be achieved.